MENJAGA KESTABILAN PANTAI DENGAN TANAMAN MANGROVE - Ricko Rivaldo Ruben Do’o; Andri Daeng Salimung; Clara Anggreini Ines Benge; Filipus Alfriyadi Junaidi; Faturrahman Jahrun Trumpi; Sely Novita Sari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Mangrove forests that used to adorn the coast, have now turned into tourist and recreational places such as hotels on the beach. Of the total 9.4 million hectares of mangrove plants in Indonesia, according to data from the Indonesian Ministry of Forestry in 2006, about 70 percent were damaged. Because the Kulongpurogo beach area is located in the south of Java Island, every year it experiences big waves and coastal erosion. Coastal erosion has eroded most of the land in the coastal area and caused losses to residents. Trisik Beach is a beach located in the west of the mouth of the Progo River. For this reason, the purpose of community service is about how to maintain beach stability with mangrove plants. The method used to describe the situation at a time that is temporarily taking place more clearly. Qualitative and quantitative descriptive analysis was carried out in this service. Qualitative analysis was used with the aim of facilitating interpretation and explanation of the results of the questionnaire in knowing the perceptions and participation of the community that were distributed during socialization, and quantitative analysis was carried out in processing the questionnaire understanding of pocket books during socialization in Tigabelas Hamlet, Banaran Village, Galur District, Kulonprogo, Special Region of Yogyakarta. The results obtained are in the form of 90% of youth groups who have been socialized about a pocket book on how to plant mangroves and increase their understanding before being given socialization